Hate-motivated crimes in Brazil: an overview of crimes against LGBTQI+ people - Ceccato, Vania; Agapito, Leonardo Simões [UNESP] (Emerald, 2024)
Purpose: This paper aims to provide an overview of the nature of hate-motivated crimes in Brazil by focusing on offenses against LGBTQI+ people and discussing the current legal approaches to combating hate-motivated crimes. Design/methodology/approach: The paper draws on secondary sources and analysis of existing literature in the field, which is primarily in the Portuguese language. Findings: There is no formal definition of hate crime in Brazil. However, it is estimated that Brazil has one of the highest rates of hate crimes perpetrated against LGBTQI+ people in the world, and lethal violence against this group has been on the increase since 2000, especially among black and brown LGBTQI+ people. In more than half of the lethal incidents in public places, often in large cities, the victims and the perpetrators are typically young. The study shows how the lack of a unified legal definition for hate-motivated crimes directly impacts LGBTQI+ people, poses challenges for organizations when collecting data on this group and highlights the need for legislation and enforcement agencies to promote transparency around hate crimes in Brazil. Research limitations/implications: The study shows how the lack of a unified legal definition for hate-motivated crimes directly impacts LGBTQI+ people, poses challenges for organizations when collecting data on this group and highlights the need for legislation and enforcement agencies to promote transparency around hate crimes in Brazil. Originality/value: The paper contributes to the literature on gender violence through the analysis of various data sources, created and disseminated by advocacy agencies and other related institutions, on hate crimes against LGBTQI+ people in Brazil.
Keywords: Discrimination; Gender; Global South; Homophobia; Queer; Violence